The blood of innocents [large type] - Lynch, Sean, active 2013- (The guns of Samuel Pritchard, 2021)
"As both a former Confederate guerilla and Texas Ranger, and now a U.S. Marshal, no one knows the dangers of the frontier and cowtowns like Marshal Samuel Pritchard. A couple of wagon trains traveling the Oregon Trail have vanished and Pritchard's got miles of bad road across hostile territory to investigate. But he must also reckon with a price on his head. Bounty hunter Captain Laird Bonner is the greatest manhunter throughout the west- and he's as ruthless as he's relentless in pursuing his prey. Then the trail for both Pritchard and Bonner ends in an Idaho mining town named Whiskey Falls. Ruled by a man who earned his stripes in Andersonville, the town is a literal hell for everyone who lives there, slaving and dying to satiate their captor's lustful greed. To escape, Pritchard and Bonner must declare an uneasy truce and take on an army of gunmen. This is the story of Samuel Pritchard. A frontier-town peacekeeper who left many outlaws dead in the dust..."--